1992
DOI: 10.1111/j.1745-6592.1992.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

The Application of In Situ Air Sparging as an Innovative Soils and Ground Water Remediation Technology

Abstract: Vapor extraction (soil venting) has been demonstrated to be a successful and cost‐effective remediation technology for removing VOCs from the vadose (unsaturated) zone. However, in many cases, seasonal water table fluctuations, drawdown associated with pump‐and‐treat remediation techniques, and spills involving dense, non‐aqueous phase liquids (DNAPLS) create contaminated soil below the water table. Vapor extraction alone is not considered to be an optimal remediation technology to address this type of contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 3 publications
0
37
0
1
Order By: Relevance
“…40, W09203, doi:10.1029/2003WR002960, 2004 aerobic biodegradation [e.g., Reddy and Adams, 2001;Brooks et al, 1999;Ahlfeld et al, 1994;Ji et al, 1993;Marley et al, 1992;Bruell et al, 1997].…”
Section: W09203mentioning
confidence: 99%
“…40, W09203, doi:10.1029/2003WR002960, 2004 aerobic biodegradation [e.g., Reddy and Adams, 2001;Brooks et al, 1999;Ahlfeld et al, 1994;Ji et al, 1993;Marley et al, 1992;Bruell et al, 1997].…”
Section: W09203mentioning
confidence: 99%
“…Air sparging can also impact the DO levels by transfer within the saturated zone due to the mixing associated with air sparging system start-up and shut-down. Following several hours of sparging, groundwater DO levels are often observed to increase significantly at one or a number of monitoring points (Marley, et al 1993). Combined air sparging and SVE systems may also influence DO levels as a result of air transport occurring within the unsaturated zone or may contribute to elevated DO levels via equilibrium between the aqueous and air phases.…”
Section: Dissolved Oxygen (Do) Monitoringmentioning
confidence: 99%
“…Experimental studies on air sparging on both field [Johnson et al, 1993;Lundegard and LaBrecque, 1995;Marley et al, 1992] and laboratory [Ji et al, 1993;Wehrle, 1990] scales intended to determine the region in the saturated zone where air is present (radius of influence). These studies revealed that variations in soil texture strongly affect the air flow.…”
Section: Introductionmentioning
confidence: 99%